Typification of the name Eranthis sibirica (Ranunculaceae) - Erst, Andrey S.; Boltenkov, Eugeny V.; Wang, Wei (Phytotaxa, 2020)
A revision of Eranthis Salisbury (1807: 303) in Siberia as part of the preliminary study revealed that the name E. sibirica Candolle (1817: 315) had not yet been typified. The present lectotypification is made with the explicit purpose to stabilize the use of the name in the sense it has been used before and is being used now.